Analisis Peran Kader Pemberdayaan Masyarakat Desa (KPMD) dalam Pembangunan Desa Berkelanjutan di Indonesia - Abdi Muhammad, Juang; Firdausi, Rohmatina; Aries Samudra Wicaksono (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
The effectiveness of the program to Village SDGs requires synergy between Village Community Institutions, especially in this research the role of Village Community Empowerment Cadres. This research aims to describe the role of Village Community Empowerment Cadres in sustainable village development in Indonesia. As well as knowing the government's efforts to develop the capacity of Kader Pemberdayaan Masyarakat Desa in Indonesia. The research method used is qualitative, descriptive in nature using policy research in accordance with existing regulations in Indonesia. The results of the research show that the role of Kader Pemberdayaan Masyarakat Desa in accelerating change or driving sustainable village development activities is quite good, as evidenced by the village community's satisfaction with Kader Pemberdayaan Masyarakat Desa's performance, both in helping to provide services, empowering, providing guidance or educating, and helping to become a problem solver. Apart from that, the government is making various efforts to increase the functional capacity of Kader Pemberdayaan Masyarakat Desa in the hope that village development can continue.